Outcomes in acute ischemic stroke patients undergoing endovascular thrombectomy: Cervical internal carotid artery pseudo-occlusion vs. true occlusion - Ni, Heng; Yang, Tao; Jia, Zhenyu; Shi, Haibin; Liu, Sheng; Zhao, Linbo (Frontiers in Neurology, 2023)
Background and purpose Pseudo-occlusion of the cervical internal carotid artery (cICA) refers to an absence of intraluminal contrast on computed tomography angiography (CTA), while the artery is patent on digital subtraction angiography during endovascular thrombectomy. We aimed to compare the outcomes between the cICA pseudo-occlusion and true occlusion after thrombectomy. Methods We retrospectively analyzed patients with apparent cICA occlusion on CTA who underwent thrombectomy between January 2016 and August 2021, and divided them into the pseudo-occlusion and true occlusion groups based on angiographic exploration. Recanalization failure was defined as a modified Thrombolysis in Cerebral Infarction score of 0–2a. Poor outcome was defined as a 90-day modified Rankin Scale score of 3–6. Propensity score matching was performed to compare the outcomes. Sensitivity analysis using multivariate-adjusted regression in the original cohort was conducted to test the robustness of the findings. Results Of the 146 patients included, 79 patients (54.1%) had cICA pseudo-occlusion and 67 patients (45.9%) had true occlusion. Following 1:1 propensity score-matched analysis, patients with pseudo-occlusion had an increased likelihood of recanalization failure (OR, 3.18; 95% CI, 1.06–9.59; P = 0.040) and poor outcome (OR, 2.80; 95% CI, 1.07–7.30; P = 0.035) compared with patients with true occlusion. Sensitivity analysis showed that cICA pseudo-occlusion remained independently associated with recanalization failure (OR, 2.55; 95% CI, 1.07–6.09; P = 0.036) and poor outcome (OR, 2.48; 95% CI, 1.08–5.67; P = 0.032). Conclusions Patients with cICA pseudo-occlusion on CTA treated with thrombectomy had an increased risk of reperfusion failure and poor outcome compared with true occlusion patients.